EKSISTENSI PERKAWINAN DI BAWAH UMUR TERHADAP PERLINDUNGAN ANAK - Karmina Siska; Putri Maha Dewi; Desi Syamsiah (Sekolah Tinggi Pariwisata Mataram, 2022)
Abstract This research is a normative legal research that only examines secondary data. Data collection techniques in this study were carried out by collecting library materials which were then analyzed using qualitative data analysis methods. The purpose of this study was to determine the impact of underage marriage on child protection. The results of this study indicate that the practice of underage marriage can cause various kinds of consequences, both positive and negative. The positive effects are avoiding adultery, helping reduce the economic burden on parents and teaching children to be responsible for responsibilities from an early age. Meanwhile, the negative impact caused is the loss of the right to education, limited association, triggering the perpetrator to experience depression, affecting health, especially for women, vulnerable to divorce and domestic violence (KDRT). This phenomenon is a deviation from the rights of children. Thus, the existence of the practice of underage marriages can cause child protection not to be implemented, especially in terms of education.